gewohnt: un/common - Gethmann, Daniel; Eckhard, Petra; Hirschberg, Urs; Petersson, Petra (GAM - Graz Architecture Magazine, 2021)
Contemporary and future forms of living together urgently need new concepts in order to respond to growing social inequality, the dissolution of traditional structures for work and the family, and the emergence of diverse patterns of social relationships. GAM.16 conceives of spatial formation as a permeable framework for sociospatial structures in various architectural, sociological, and cultural contexts, aiming to increase awareness of common resources and again make them one focus of sociopolitical discourse. Themed "gewohnt: un/common," GAM.16 advocates for communal living and introduces collaborative and coproductive concepts of organization as a spatial practice. With contributions by Massimo Bricocoli, Heike Delitz, Marson Korbi, Nikolai Roskamm, Sabine Storp, Fritz Strempel, and others